The Factors Influencing Tea Consumers’ Attitude in Banyumas Regency - Muthia Auralia; Any Suryantini; Jangkung Handoyo Mulyo (Jurnal Manajemen & Agribisnis, 2023)
Tea producers need to understand consumer perceptions of product attributes and consumer attitudes to face tough competition The large selection of products marks the lifestyle of the people in Banyumas Regency consuming tea every day. The research objective was to analyze the effect of scent, taste, brew color, brand, and price on consumer attitudes. The research locations were selected using purposive method, namely Sokaraja District and South Purwokerto Regency because they have the largest population and housing development in Banyumas Regency. The data collection through interviews with 175 tea consumer respondents was selected by convenience sampling, namely consumers who consumed black tea in packs of original tea bags and/or jasmine tea and made purchasing decisions within the household. The analytical method uses structural equation modelling to analyze the factors that influence consumer attitudes. Mostly, tea consumers are women with an average age of 43 years, are married with an undergraduate level of education, and have a household income above IDR 1,970,000. The results showed that floral scent, astringent taste, reddish brown brew color, brand popularity, and affordability price could explain consumer-perceived product attributes, and consumers' evaluation of various product choices could explain consumer attitudes. Consumer perception of taste and brand positively influences consumers. Tea producers should pay attention to consumers' perceived astringent taste of brewed tea and brand popularity because the consumer considers tea's two indicators important attributes. Keywords: consumer perceptions, tea scent, tea taste, tea brew colour, consumer attitudes